Pregnancy with thalassemia: challenges and outcomes - Berwal, Vidhika; Kyal, Amit; Dessa, Dorothy; Bhowmik, Joyita; Mondal, Payel; Mukhopadhyay, Partha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Thalassemia syndromes are autosomal recessive disorders and the most commonly inherited haemoglobinopathies in the world. HbE β is the most common type of thalassemia in eastern India. The objectives of the study include maternal outcome and complications like anemia, hypertensive disorders, gestational diabetes mellitus and also to study the neonatal outcome in terms of low birth weight, prematurity and other complications. Methods: A prospective longitudinal study carried out over a period of one year from July 2016 to June 2017 in Medical College, Kolkata. Fifty antenatal thalassemic mothers over 20 weeks of gestation during study period were enrolled in after institutional ethical clearance and consent from study subjects. All necessary investigations (complete haemogram, reticulocyte counts, Ultrasounds etc.) were done followed by statistical analysis. Results: Out of total 50 diagnosed thalassemic patients, maximum were HbE Beta Thal i.e. 54.0%. The mean level of iron in these women varied from 95.70±17.16µg/dl to 99.46±18.19µg/dl at the time of delivery and ferritin varied from 185.40±49.26µg/L vs 194.13±48.80µg/L. The mean blood transfusion done was 6.84 Units. Incidence of maternal complications were variable, PIH was found to be 26% whereas it was just 8% for GDM. The mean gestational age at delivery (Mean±SD) was 36.30±2.08 weeks. NICU admission was high (50%). Conclusions: Pregnancy with thalassemia is considered high risk, continuous pre-conceptional, antenatal and postpartum assessment should be done for favorable outcomes.